Pengetahuan Ibu Berhubungan dengan Pelaksanaan Toilet Training pada Anak Usia 3-5 Tahun di PAUD Islam Cerliana Kota Pekanbaru Tahun 2016 - Sherly Vermita Warlenda; Rini Novita Sari (STIKes Hang Tuah Pekanbaru, 2017)
Toilet training to children is an effort to train the children to be able to control the urinate and defecate process. Toilet training can conduct to children on 18 months-2 years old. In this training, children needs preparation physically, psychologically and intellectually, So children expected to be able to control the urinate and defecate by them selves. The study aims is to find out the correlation between knowledge, education level, occupation and mother’s ages with the implementation of toilet training to children. This was a quantative analytical study with cross sectional approach. The samples were 41 respondents in early childhood Cerliana Islam. The sampling was used saturated sampling techniques. The data collection was used quesonnaires. The data analyze was an univariate and bivariate with chi-square test at the 95% confidence level used a computer program. The results showed. There was a significant correlation between mother’s knowledge (p = 0.00), with the implementation of toilet training in children aged 3-5 years in early childhood Islam Cerliana Pekanbaru. It is recommended to mother to train their children to urinate and defecate in the toilet early. The other side, it is recommended to school especially teachers to teach toilet training early to children by avoid the use of diapers.